The Role of Education in Achieving Sustainable Development (Singapore is a Model) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
Development depends on many factors, including capital, natural resources, technical progress, political, social, cultural and economic conditions, and the degree of awareness of members of society. Development needs are not limited, but it depends mainly on the manpower needed. In view of the fact that development projects depend to a large extent on the provision of its needs of individuals according to the required skill levels, thus we must give high priority to education in all its stages and levels, meeting its requirements, fulfilling its requirements, and allocating a large part of the state budget to it; all that because of its impact and the close link between its level and the ranking of the state in the development ladder. Development must be all-encompassing and sustainable, where real and effective development is not confined to one side, since development must be comprehensive in its economic and social aspects, with its various axes and elements including health, education, employment, adequate income, satisfaction of basic needs and the ability to give and innovate. تعتمد التنمية على عوامل عديدة من ضمنها رأس المال، الموارد الطبيعية، والتقدم التقني والظروف السياسية والاجتماعية والثقافية والاقتصادية، ودرجة الوعي لدى أفراد المجتمع، فحاجات التنمية لا تنحصر. ولكنها تعتمد أساساً على القوى البشرية اللازمة. ومن منطلق أن مشاريع التنمية تتوقف إلى حد بعيد على توفير حاجاتها من الأفراد وفق مستويات المهارة المطلوبة فيجب إيلاء أهمية وأهمية شديدة للتعليم بكافة مراحله ومستوياته وإيفاء متطلباته. وصرف وتخصيص قسم كبير من ميزانية الدولة له لما له من أثر وارتباط وثيق بين مستواه وترتيب الدولة على سلم التنمية. ويجب كذلك الأمر أن تكون التنمية شاملة بكافة أنواعها وأن تكون كذلك مستدامة. فالتنمية الحقيقية والفعالة لا تقتصر على جانب دون آخر، إذ يجب أن تكون التنمية شاملة في جوانبها الاقتصادية والاجتماعية وما تتضمنه من محاور وعناصر عديدة تشمل الصحة التعليم والعمل والدخل الكافي وإشباع الحاجات الأساسية والقدرة على العطاء والإبداع.